2016
DOI: 10.1101/cshperspect.a026443
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Mechanisms of Histone H3 Mutations

Abstract: Recurrent missense mutations in histone H3 were recently reported in pediatric gliomas and soft tissue tumors. Strikingly, these mutations only affected a minority of the total cellular H3 proteins and occurred at or near lysine residues at positions 27 and 36 on the amino-terminal tail of H3 that are subject to well-characterized posttranslational modifications. Here we review recent progress in elucidating the mechanisms by which these mutations perturb the chromatin landscape in cells through their effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 74 publications
0
49
0
Order By: Relevance
“…Notably, these mutations occur at, or near, two key lysine residues (K27 and K36) involved in chromatin regulation and collectively, these and other histone mutations found in cancer are referred to as "oncohistones." [2] The K27M mutation on H3.3 induces a dramatic loss of trimethylation at Lys27 (H3K27me3) and global reprogramming of regulatory histone modifications in pediatric brain cancers [3]. Interestingly, this study showed that although the H3.3K27M oncohistone comprised only a small fraction of the total H3 in cells, it mediated loss of global H3K27me3 in a dominant negative manner, depleting this mark from the majority of endogenous H3.…”
Section: Introductionmentioning
confidence: 81%
“…Notably, these mutations occur at, or near, two key lysine residues (K27 and K36) involved in chromatin regulation and collectively, these and other histone mutations found in cancer are referred to as "oncohistones." [2] The K27M mutation on H3.3 induces a dramatic loss of trimethylation at Lys27 (H3K27me3) and global reprogramming of regulatory histone modifications in pediatric brain cancers [3]. Interestingly, this study showed that although the H3.3K27M oncohistone comprised only a small fraction of the total H3 in cells, it mediated loss of global H3K27me3 in a dominant negative manner, depleting this mark from the majority of endogenous H3.…”
Section: Introductionmentioning
confidence: 81%
“…The multiple gene copies in these clustered arrays are sometimes confusingly referred to as "allelic" and the resulting combined protein isoforms are often considered to be "wild type" although both genes and protein products display variation in primary sequence and relative abundance, and their functional equivalence has not been tested. A number of mutations in individual canonical and variant histone genes have been revealed to contribute to cancer [12,21]. These "oncohistones" demonstrate that single amino acid changes in individual histone genes can have functional implications.…”
Section: Genomic Perspectivementioning
confidence: 99%
“…Recent high-throughput sequencing studies have identified specific recurrent mutations in histone proteins in a number of human neoplasms. 74 The consequences of these mutations have been studied in several cases, and they appear to globally alter the deposition of histone post-translational modifications, leading to changes in gene expression. For example, diffuse intrinsic pontine glioma is characterized by recurrent H3K27M mutations in H3.3, a histone H3 variant.…”
Section: Mutations In the Histones Themselves: Giant Cell Tumor Of Bomentioning
confidence: 99%